EKOSISTEM ETIKA PERGURUAN TINGGI ISLAM SEBAGAI PARADIGMA PEMBINAAN SIVITAS AKADEMIKA DALAM MERESPONS DINAMIKA MORAL KONTEMPORER DI ACEH - Anita Anita (Lembaga Sepercenter, 2026)
Contemporary moral dynamics in Aceh indicate that the existence of regulations and law enforcement is not fully sufficient to foster moral awareness and character development in a sustainable manner. Issues such as sexual violence, drug abuse, harmful use of digital media, and other social problems have legal as well as educational, cultural, and ethical dimensions. This article aims to formulate a conceptual model of the Islamic Higher Education Ethical Ecosystem as a paradigm for developing academic community members in responding to contemporary moral dynamics in Aceh. The study employs a library research method with a qualitative-conceptual approach. Data were obtained from relevant regulations, books, scholarly articles, and official documents and were analyzed through content analysis and conceptual analysis. The findings indicate that the ethical ecosystem is constructed through the interrelationship of four main elements: character education, academic culture, da'wah as ethical praxis, and institutional collaboration. These four elements are oriented toward the realization of public welfare (maṣlaḥah) from the perspective of maqāṣid al-sharī‘ah. In this model, Islamic higher education institutions are not positioned as law-enforcement institutions, but as centers of value transformation through education, research, community engagement, and the development of academic culture. This article offers a conceptual contribution in the form of the Islamic Higher Education Ethical Ecosystem as a preventive paradigm that connects individual development, institutional culture, and social collaboration in fostering academic communities that are knowledgeable, virtuous, academically integrated, and socially responsible.